Economic Analysis of Crypto Asset Regulation in Indonesia: Market Impact, Investor Behavior and Islamic Economic Perspective - Nanda Nur Sofyana (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The transfer of crypto asset regulatory authority from Bappebti to the Financial Services Authority (OJK) in 2025 represents a policy transformation with significant economic consequences for Indonesia's digital financial market. This article presents a narrative literature review analyzing three economic dimensions of this regulatory change: (1) the impact of regulation on market dynamics and crypto asset price volatility; (2) the response and behavior of crypto investors in Indonesia amidst the changing regulatory landscape; and (3) the implications of regulation from an Islamic economic perspective based on the 2021 Ijtima Ulama. The review results indicate that: first, regulations that increase legal certainty have the potential to suppress short-term volatility while encouraging long-term institutional adoption, although empirical evidence suggests that the announcement of regulations was initially responded negatively by market players; second, the growth of Indonesian crypto investors, reaching more than 21 million by 2024, is driven by digital financial literacy, risk perception, and speculative motives, which require a policy approach based on economic education; Third, the 2021 Ijtima Ulama fatwa places crypto assets in a conditional position from an Islamic economic perspective, namely, they are forbidden as a medium of exchange but offer opportunities as conditional investment assets. Therefore, OJK regulations need to accommodate the evolving needs of Muslim investors. This article identifies a research gap in the form of a lack of empirical studies on the macroeconomic impact of crypto regulations in Indonesia and the need for a regulatory model that integrates Islamic economic principles.